Case Report: Diagnosis, treatment and follow-up of venous thrombosis in adolescent diabetic patients with SARS-CoV-2 - Ma, Fanshu; Zhang, Qiang; Pei, Li; Shuai, JinFeng; Li, Jinying (Frontiers in Pediatrics, 2025)
The highest risk of diabetes mellitus (DM)-related complications, collectively known as venous thromboembolism (VTE), is observed in the age group of 20–39 years. However, this observation sharply contrasts with the increased incidence of superficial venous thrombosis observed among adolescent patients during the coronavirus disease 2019 (COVID-19) outbreak in Hebei Province in December 2022. Moreover, it contradicts the absence of venous thrombosis observed in pediatric diabetic patients who were treated prior to the COVID-19 outbreak. This study collected and analyzed clinical data related to diabetic venous thrombosis in children, with the aim of provide evidence for the prevention and treatment of this complication.